Penggunaan Lirik Lagu Berbahasa Inggris dalam Peningkatan Kemampuan Berbahasa Siswa - Lasut, Elizabeth; Assa, Amelia Melisa (DIDASCO, 2024)
The use of English song lyrics to improve students' English language skills at the elementary level is interesting to be investigated. This quantitative-descriptive research illustrates the benefits that Airmadidi Adventist Elementary School students can gain through learning using English song lyrics. By involving 60 sixth grade elementary school students as respondents, data was collected through a questionnaire regarding the use of song lyrics which was distributed to students. Data analysis was carried out using statistical means of average values ​​and the results obtained showed that the use of English song lyrics during learning was useful in improving listening skills, the ability to pronounce vocabulary accurately and correctly, as well as the ability to increase students' vocabulary. With the results obtained, it can be concluded that learning English becomes more optimal if it is accompanied by using English song lyrics in learning. That is why, it is recommended for English subject teachers to integrate the use of English song lyrics when teaching subject matter because of the benefits students can get in improving their ability to listen and pronounce English vocabulary, and even increase their vocabulary.